MAINTAINING FAMILY PRIVACY AND SECURITY IN THE DIGITAL AGE - Akbar, Aldi; Kuswanto, Arif; Rustandi Kartawinata, Budi (PT. Jurnal Center Indonesia Publisher, 2025)
This activity aims to provide parents and teachers of Pandanwangi PAUD with a basic understanding of the importance of maintaining privacy and security in the use of digital technology, as well as providing practical guidance on how to protect personal information and secure digital devices used by family members. The methods used in this educational activity are lectures, group discussions, and case simulations. The results of this educational activity show that the participants have a better understanding of the importance of maintaining family privacy and security in the digital era, are more aware of the risks in cyberspace and are able to identify and overcome these threats better. The conclusion of this activity is that education about digital privacy and security is very important to be given to the community, especially parents and teachers who have a big role in educating children.